2013
DOI: 10.1128/mcb.00959-13
|View full text |Cite
|
Sign up to set email alerts
|

CREB3L1 Is a Metastasis Suppressor That Represses Expression of Genes Regulating Metastasis, Invasion, and Angiogenesis

Abstract: The unfolded protein response (UPR) is activated in response to hypoxia-induced stress such as in the tumor microenvironment. This study examined the role of CREB3L1 (cyclic AMP [cAMP]-responsive element-binding protein 3-like protein 1), a member of the UPR, in breast cancer development and metastasis. Initial experiments identified the loss of CREB3L1 expression in metastatic breast cancer cell lines compared to low-metastasis or nonmetastatic cell lines. When metastatic cells were transfected with CREB3L1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 47 publications
4
61
0
Order By: Relevance
“…CREB3L1 binds promoter regions of angiogenic genes, such as prostaglandin E synthase, fibroblast growth factor-binding protein 1, or chemokine (C-X-C motif) ligand 10 (CXCL10), and represses their transcription. Hence, induction of CREB3L1 will be detrimental for tumor growth, in part by compromising tumor angiogenesis (Mellor et al, 2013). CREB3L1 could thus work against other pathways of the UPR, such as ATF4 and IRE1a, which drive expression of pro-angiogenic genes but can also trigger proapoptotic arms of the UPR (Sano and Reed, 2013).…”
Section: Upr In Tumor Angiogenesismentioning
confidence: 97%
See 1 more Smart Citation
“…CREB3L1 binds promoter regions of angiogenic genes, such as prostaglandin E synthase, fibroblast growth factor-binding protein 1, or chemokine (C-X-C motif) ligand 10 (CXCL10), and represses their transcription. Hence, induction of CREB3L1 will be detrimental for tumor growth, in part by compromising tumor angiogenesis (Mellor et al, 2013). CREB3L1 could thus work against other pathways of the UPR, such as ATF4 and IRE1a, which drive expression of pro-angiogenic genes but can also trigger proapoptotic arms of the UPR (Sano and Reed, 2013).…”
Section: Upr In Tumor Angiogenesismentioning
confidence: 97%
“…Later, silencing pro-apoptotic arms of the UPR, such as CREB3L1 or CHOP, would ensure maintenance of tumor vasculature (Mellor et al, 2013) and might be beneficial for tumor survival (Sano and Reed, 2013).…”
Section: Upr In Tumor Angiogenesismentioning
confidence: 99%
“…These studies suggest that tumors with high levels of Creb3L1 expression are more likely to respond to treatment with doxorubicin than those that do not express Creb3L1 (Denard et al, 2012). In mammary cancer lines, Creb3L1 is downregulated in highly metastatic cancers (Mellor et al, 2013). Mellor et al recently found that mammary cancer cells that do express Creb3L1 are less invasive, less migratory and are more sensitive to hypoxia-induced apoptosis.…”
Section: Creb3l1/oasismentioning
confidence: 99%
“…Mellor et al recently found that mammary cancer cells that do express Creb3L1 are less invasive, less migratory and are more sensitive to hypoxia-induced apoptosis. Microarray analysis revealed a number of genes regulated by Creb3L1 that control cell proliferation and apoptosis (Mellor et al, 2013). Correspondingly, injection of cancer cells expressing Creb3L1 into mice resulted in smaller tumors and, in 70% of the mice, the tumor actually regressed in size (Mellor et al, 2013).…”
Section: Creb3l1/oasismentioning
confidence: 99%
“…Human breast adenocarcinoma estrogen receptor-positive MCF-7 and T-47D, and estrogen receptor-negative MDA-MB-231 and MDA-MB-435 cell lines were obtained from American Type Culture Collection (Manassas, VA, USA). There is controversy as to the origin of the MDA-MB-435 cell line in that it is identical to the M14 melanoma cell line at the karyotypic level; however, evidence of secretion of milk proteins and the presence of two X chromosomes from this cell line would indicate that it is derived from the mammary epithelium of a human female thus making it uncertain and controversial as to whether these cells originated from human breast adenocarcinoma or melanoma [32,33]. Breast cancer tumor tissues for microarray analysis were obtained from the Neag Cancer Center of the University of Connecticut Health Center (UCHC) in a deidentified manner.…”
Section: Breast Cancer Cells and Tissuesmentioning
confidence: 96%